Treadmill exercise ameliorates Alzheimer disease-associated memory loss through the Wnt signaling pathway in the streptozotocin-induced diabetic rats - Kim, Dae-Young; Jung, Sun-Young; Kim, Kijeong; Kim, Chang-Ju (Journal of exercise rehabilitation, 2016)
Diabetes mellitus is considered as a risk factor for Alzheimer disease. The aim of the present study was to evaluate the possibility whether treadmill exercise ameliorates Alzheimer disease-associated memory loss in the diabetes mellitus. For this study, the effects of treadmill exer-cise on short-term memory and spatial learning ability in relation with Wnt signaling pathway were evaluated using the streptozotocin (STZ)- induced diabetic rats. Diabetes was induced by intraperitoneal injection of STZ. Step-down avoidance task and 8-arm radial maze test were performed for the memory function. Immunohistochemistry for 5-bro-mo-2‘-deoxyridine (BrdU) and doublecortin (DCX) and Western blot for Wnt3 and glycogen synthase kinase-3β (GSK-3β) were conducted. The rats in the exercise groups were made to run on the treadmill for 30 min per one day, 5 times a week, during 12 weeks. In the present results, short-term memory and spatial learning ability were deteriorated by in-duction of diabetes. Treadmill exercise improved short-term memory and spatial learning ability in the diabetic rats. The numbers of BrdU -positive and DCX-positive cells in the hippocampal dentate gyrus were decreased by induction of diabetes. Treadmill exercise increased these numbers in the diabetic rats. Wnt3 expression in the hippocampus was decreased and GSK-3β expression in the hippocampus was increased by induction of diabetes. Treadmill exercise increased Wnt3 expression and suppressed GSK-3β expression in the diabetic rats. The present study suggests that treadmill exercise alleviates Alzheimer disease-as-sociated memory loss by increasing neurogenesis through activating Wnt signaling pathway in the diabetic rats.